Redescription of Libanasa brachyura Karny, 1928. (Orthoptera: Anostostomatidae: ?Lutosinae) from Tanzania and problems at the subfamily level - Johns, Peter M.; Hemp, Claudia (Zootaxa, 2015)
Libanasa brachyura Karny, 1928 is resurrected and redescribed. Morphological details are added which now question its placement in the Lutosinae, and this in turn questions the subfamily arrangements as a whole. New characters are introduced for future comparison with other genera. Some details of its biology are also added.